Monitoring stress and recovery: new insights for the prevention of injuries and illnesses in elite youth soccer players - Brink, M. S.; Visscher, C.; Arends, S.; Zwerver, J.; Post, W. J.; Lemmink, K. (British Journal of Sports Medicine, 2010)
Objective: Elite youth soccer players have a relatively high risk for injuries and illnesses due to increased physical and psychosocial stress. The aim of this study is to investigate how measures to monitor stress and recovery, and its analysis, provide useful information for the prevention of injuries and illnesses in elite youth soccer players.